Phenytoin- and amlodipine-induced gingival overgrowth - Ching-Wen Chang; Chih-Jen Yang; Yu-Lin Lai (Journal of Dental Sciences, 2012)
Drug-induced gingival overgrowth is an adverse event associated with three types of drugs, i.e., anticonvulsants, immunosuppressants, and calcium-channel blockers. It was shown that the combined use of an immunosuppressant (cyclosporine) and a calcium-channel blocker increases the prevalence and severity of gingival overgrowth. However, few reports discussed the effects of the combination of an anticonvulsant (phenytoin) and a calcium-channel blocker (amlodipine). In this case report, we present an epilepsy patient who was using both phenytoin and amlodipine, which caused extensive gingival overgrowth. After periodontal treatment and a gingivectomy, the gingival overgrowth was significantly reduced. A postoperative drug-substitution regimen and intensive professional care ensured a stable result 1 year after surgery.